On stochastic equations for nonlinear filtering problem of stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. О стохастических уравнениях нелинейной фильтрации случайных процессовB. Grigelionis. Apie atsitiktinių procesų netiesinės filtracijos stochastines lygtis